AUDITOR INDEPENDENCE IN THE VORTEX OF CONFLICT OF INTEREST: A FORTRESS OF DEFENSE OR A MERE ILLUSION OF COMPLIANCE - Rahmad Haqqi; Yusnaini Yusnaini (PT. Media Akademik Publisher, 2026)
Auditor independence is the cornerstone of financial reporting integrity, yet its position is frequently threatened by conflicting interests. This study aims to map how auditor independence stands as a